A case study on the application of Batas Pambansa Bilang 344 in selected high-rise residential condominium building - Balonan, Kimberly Anne O.; Mayo, Adelaida Villaraza (Quezon City UP College of Home Economics, 2012)
This case study sought to determine whether the selected high-rise residential condominium buildings in Pasig and Makati City had fulfilled the minimum requirements stipulated in Batas Pambansa Bilang 344 (BP 344). Specifically, the study evaluated the existing interior design features of the chosen buildings following the guidelines of BP 344, and established the common provisions fulfilled and violated by the selected condominium buldings. Through convenience sampling three condominium buildings served as the sample of this study and were referred to as Condominium A, B, C. The interior design features examined in these buildings include the following: entrances, ramps, doors, thresholds, switches, signages, corridors, washrooms and toilets, stairs, and elevators. Results show that the three buildings have very similar interior design features. 9 out of 10 features inside the Condominiums were assessed to have not provided accessible interior design features and facilities. Currently, the BP 344 is still not priority of buildings and establishments especially high-rise residential buildings. With this in mind, this study would be a significant contribution to the individuals of the design field, to the curriculum of the Bachelor in Science in Interior Design, and to the individuals who are concerned and challenged to provide those people with disabilities an equal opportunity to be part of the society.
Thesis (BSID)--University of the Philippines Diliman
Keywords: Architecture and the physically handicapped -- Case studies; Building design and the physically handicapped -- Case studies